Peran e-SAKIP dalam Penguatan Tata Kelola Pemerintahan Daerah: Studi di Kota Palembang pada Era Revolusi Industri 4.0 - Pandu Pamungkas; Zetia Wijayanti; Adelia Maharani; Metta Karuna; Ani Santia; Tegar Victor Pratama Aritonang (MAN 4 Kota Pekanbaru, 2026)
This study explores the role of e-SAKIP (Electronic-Based Government Performance Accountability System) digitalization in supporting the economic and political transformation of Palembang City amidst the Industry 4.0 era, utilizing a literature review approach. The research synthesizes data from credible sources, including official government documents, academic journals, news reports, and case studies focusing on transparency, accountability, efficiency, and planning optimization. That e-SAKIP enhances governance through real-time data access, improves public service delivery, and boosts regional competitiveness, as evidenced by Palembang’s 2024 SAKIP Award (BB predicate). However, challenges such as infrastructure limitations, low human resource competency, and dual reporting systems hinder full implementation. The study aligns with Industry 4.0 trends, emphasizing the need for integrated technology and workforce development to sustain economic-political growth, offering practical insights for policy reform and academic contributions to digital governance literature.